Pengaruh Struktur Modal, Ukuran Perusahaan, Profitabilitas Dan Kebijakan Dividen Terhadap Nilai Perusahaan - Burhan, Akbar H; Bagana, Batara Daniel (Owner : Riset dan Jurnal Akuntansi, 2024)
This study aims to analyze and examine the factors that influence firm value. The variables used in this study are capital structure, company size, profitability and dividend policy. The analytical method used in this study is the quantitative analysis method. The population of this study are manufacturing companies in the various industrial sectors listed on the Indonesia Stock Exchange in 2019-2022. The method used in data collection is purposive sampling method. The number of samples used were 35 companies and the amount of data used was 140 data. When processing data, there are several company data that must be outliers. After the outlier data, the number of samples used was 91 data. The analytical method used in this study is the quantitative analysis method. The results showed that profitability has a positive effect on firm value. Capital structure, company size and dividend policy have no effect on firm value.